2019
DOI: 10.1016/j.jgo.2018.07.002
|View full text |Cite
|
Sign up to set email alerts
|

First validation of the G-8 geriatric screening tool in older patients with glioblastoma

Abstract: Here, we highlighted the possibility of using the G8 score, with possibly three cut-offs, in the management of older patients with glioblastoma and determined the prognostic role of this quick and easy screening tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Interestingly, frail patients received only 2.8 cycles of temozolomide after chemoradiotherapy due to progressive disease, toxicity, or death. Although KPS is a well-established prognostic factor for glioblastoma patients and we showed an association between KPS and CGA categories, CGA is a useful instrument which adds information to the performance status in the decision making for elderly cancer patients [9,30,31]. In our series, 47% of patients who were deemed frail at CGA had a good KPS between 70 and 100.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Interestingly, frail patients received only 2.8 cycles of temozolomide after chemoradiotherapy due to progressive disease, toxicity, or death. Although KPS is a well-established prognostic factor for glioblastoma patients and we showed an association between KPS and CGA categories, CGA is a useful instrument which adds information to the performance status in the decision making for elderly cancer patients [9,30,31]. In our series, 47% of patients who were deemed frail at CGA had a good KPS between 70 and 100.…”
Section: Discussionmentioning
confidence: 60%
“…Our study, compared to that of Fiorentino and colleagues, was based on a more representative patient population, given the higher sample size, and took into account all the potentially impaired domains in elderly patients, not just comorbidity, allowing for a more precise patient classification. Recently, Deluche et al [30] demonstrated the role of the screening tool G8 in predicting prognosis in elderly patients with newly diagnosed glioblastoma; they reported a median OS of 8.0 months in patients with abnormal G8 score and 42 months in those with a normal G8 score ( p < 0.0001). Although patients with impaired G8 had a HR of 10.27, the difference in overall survival was too wide between the two groups of patients (∆ = 34 months); therefore for a better identification of patients with a poor prognosis, the authors classified the patients into 3 categories (low, intermediate, and high score group), demonstrating a statistically different OS among these groups; however, contrary to expectations, “intermediate” patients reported a higher HR compared to those of the high score group (55.46 versus 8.6, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tools such as the European Organisation for Research and Treatment of Cancer GBM calculator (https://www.eortc.be/tools/ gbmcalculator/) and the Geriatric 8 (G8) scale can help in objective decision making and ensuring that decisions are not based on chronologic age alone. 14 Isocitrate dehydrogenase-wildtype (IDHwt) gliomas constitute the majority of high-grade tumors in adult neurooncology patients. These tumors can grow rapidly in short periods of time, and deferral of therapy beyond the anticipated length of the pandemic carries a high risk of tumor growth, increased neurological morbidity, and in some cases, earlier death.…”
Section: Assess Risk and Benefit Of Therapeutic Interventions In Adulmentioning
confidence: 99%
“…Median survival was 4 months in the low score group, 15 months in the intermediate score group, and 42 months in the high score group. The G8 score was identified as a significant independent prognostic factor, showing a potential role of this simple score to guide the therapeutic decision (Deluche et al 2019). Other scores such as the Charlson comorbidity index and the Instrumental Activities of Daily Living questionnaire are also available.…”
Section: Managementmentioning
confidence: 99%